2017
DOI: 10.18203/2394-6040.ijcmph20174250
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practice regarding diabetes and hypertension among elderly patients attending medicine out-patient department at Guru Nanak Dev Hospital, Amritsar

Abstract: Background: According to the WHO fact sheet 2015, non-communicable diseases kill 38 million people each year globally. This preliminary study was undertaken in order to bring about healthy ageing. Methods: It is an observational study on 100 patients above 60 years of age belonging to the rural/urban community coming to the medicine OPD on a walk-in basis in the Government Medical College, Amritsar. Results: Out of the total 100 patients, 56 were male and 44 were female. Their awareness level was recorded on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Similar study conducted by Kaur et al, found that among 100 elderly patients 93 were aware of both hypertension and diabetes. Among 61 hypertensives, 52 knew the symptoms and among 42 diabetics, 25 knew the symptoms 10.…”
mentioning
confidence: 99%
“…Similar study conducted by Kaur et al, found that among 100 elderly patients 93 were aware of both hypertension and diabetes. Among 61 hypertensives, 52 knew the symptoms and among 42 diabetics, 25 knew the symptoms 10.…”
mentioning
confidence: 99%